Phonological Transformation Of Fusha To ‘Ammiyah Egypt: Case Study On Sabry Aleel Song : At-Tahawwul aṣ-Ṣawtī min al-Fuṣḥā ilā al-‘Āmmiyyah al-Miṣriyyah: Dirāsah Ḥālah ‘alā Ughniyat Ṣabry Aleel - Ulinnuha, Nur Atika Rima; Tulus Musthofa; Mhd. Rizalman (An-Nahdah Al-'Arabiyah, 2025)
This article examines the phonological change from Fusha Arabic to Egyptian dialect ('Ammiyah) in the context of the song "Sabry Aleel." This study aims to identify and describe the sound changes that occur when song lyrics are sung in the 'Ammiyah dialect compared to Fusha Arabic. The research methods used are descriptive and phonological analysis, with data collected through the observation-note method. The results of the study showed that the change in sound from Fusha to 'Ammiyah reflected social interaction and cultural dynamics in Egyptian society. Music plays an important role as a medium of cultural expression that allows local dialects to become closer to the daily lives of listeners. The phonetic changes found included simplification of consonant and vowel pronunciation, reflecting language adaptations for ease of communication. From a sociolinguistic perspective, phonological changes not only reflect shifts in the structure of language, but also describe power relations, identity, and social integration. The use of 'Amiyah in songs can be seen as a form of resistance to Fusha's dominance, which is often associated with formal status, education, and power. In contrast, 'Ammiyah presents a local identity that is more inclusive and relevant to people's daily experiences. تتناول هذه المقالة التغيرات الفونولوجية من اللغة العربية الفصحى إلى اللهجة المصرية (العامية) في سياق أغنية صبري قليل. وتهدف هذه الدراسة إلى تحديد ووصف التغيرات الصوتية التي تحدث عند غناء كلمات الأغنية باللهجة العامية مقارنةً باللغة العربية الفصحى. وتعتمد هذه الدراسة على المنهج الوصفي والتحليل الفونولوجي، حيث تم جمع البيانات من خلال أسلوب الملاحظة والتدوين. أظهرت نتائج الدراسة أن التغيرات الصوتية من الفصحى إلى العامية تعكس التفاعل الاجتماعي والديناميكيات الثقافية في المجتمع المصري. وتلعب الموسيقى دورًا مهمًا كوسيلة للتعبير الثقافي، مما يسمح للهجات المحلية بأن تصبح أقرب إلى الحياة اليومية للمستمعين. وتشمل التغيرات الفونيتية التي تم رصدها تبسيط نطق الحروف الساكنة والحركات، مما يعكس تكيف اللغة لتسهيل عملية التواصل. من منظور علم الاجتماع اللغوي، لا تعكس التغيرات الفونولوجية مجرد تحولات في بنية اللغة فحسب، بل تصف أيضًا علاقات القوة، والهوية، والاندماج الاجتماعي. ويمكن اعتبار استخدام العامية في الأغاني شكلًا من أشكال المقاومة لهيمنة الفصحى، التي غالبًا ما ترتبط بالمكانة الرسمية، والتعليم، والسلطة. وعلى النقيض من ذلك، تعبر العامية عن هوية محلية أكثر شمولًا وارتباطًا بالتجارب اليومية للمجتمع. Artikel ini mengkaji perubahan fonologis dari bahasa Arab Fusha ke dialek Mesir (‘Ammiyah) dalam konteks lagu Sabry Aleel. Penelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan perubahan bunyi yang terjadi ketika lirik lagu dinyanyikan dalam dialek ‘Ammiyah dibandingkan dengan bahasa Arab Fusha. Metode penelitian yang digunakan adalah deskriptif dan analisis fonologis, dengan data yang dikumpulkan melalui metode observasi dan pencatatan. Hasil penelitian menunjukkan bahwa perubahan bunyi dari Fusha ke ‘Ammiyah mencerminkan interaksi sosial dan dinamika budaya dalam masyarakat Mesir. Musik memainkan peran penting sebagai media ekspresi budaya yang memungkinkan dialek lokal menjadi lebih dekat dengan kehidupan sehari-hari pendengar. Perubahan fonetik yang ditemukan meliputi penyederhanaan pengucapan konsonan dan vokal, yang mencerminkan adaptasi bahasa untuk kemudahan komunikasi. Dari perspektif sosiolinguistik, perubahan fonologis tidak hanya mencerminkan pergeseran dalam struktur bahasa, tetapi juga menggambarkan relasi kekuasaan, identitas, dan integrasi sosial. Penggunaan ‘Ammiyah dalam lagu dapat dilihat sebagai bentuk perlawanan terhadap dominasi Fusha, yang sering dikaitkan dengan status formal, pendidikan, dan kekuasaan. Sebaliknya, ‘Ammiyah menghadirkan identitas lokal yang lebih inklusif dan relevan dengan pengalaman sehari-hari masyarakat.